PREVALENSI VIRURIA SITOMEGALOVIRUS PADA POPULASI ORANG DEWASA NORMAL - Dita Ria Selvyana; Praseno Praseno; Ning Rintiswati (Universitas Islam Indonesia, 2005)
ABSTRACTThe aim of this study was to get cytomegalovirus viruria prevalence data in healthy adultpopulation. Urine samples were obtained from healthy individuals. Preparation of sample and sera(polyclonal antibody) were performed by standard method., and detection of cytomegalovirusantigen in urine sediment were done by Indirect Immunofluorescence Antibodi Technique (IFAT).The results were analyzed with chi square pearson. From 341 healthy individuals (16 ♀ and 125 ♂)age between 18 to 61 years. Cytomegalovirys viruria were found in 5 (3, 55%) of subjects. In groupof subjects less than 30 years of age, cytomegalovirus viruria were found in 3,82% subject whereasin group of subjects more than 30 years of age, cytomegalovirus viruria was not found; chi squarepearson statistic analysis did not show significant difference between two groups (p = 0,529). Ingroup of women, cytomegalovirus viruria were found in 6,25% subjects whereas in group of men,cytomegalovirus viruria were found in 3,2% subjects; chi square pearson statistic analysis did notshow significant difference between two groups (p = 0,535). Cytomegalovirus viruria prevalenceamong healthy adult population studied was relatively low (3,55%).Key words: Cytomegalovirus, viruria, prevalence, latent infection, Indirect ImmunofluorescenceAntibodi Technique (IFAT)